A Systematic Review of Efficacy, Safety, and Tolerability of Duloxetine - Rodrigues-Amorim, Daniela; Olivares, José Manuel; Spuch, Carlos; Rivera-Baltanás, Tania (Frontiers in Psychiatry, 2020)
Duloxetine is a serotonin-norepinephrine reuptake inhibitor approved for the treatment of patients affected by major depressive disorder (MDD), generalized anxiety disorder (GAD), neuropathic pain (NP), fibromyalgia (FMS) and stress incontinence urinary (SUI). These conditions share parallel pathophysiological pathways, and duloxetine treatment might be an effective and safe alternative. Thus, a systematic review was conducted following the 2009 Preferred Reporting Items (PRISMA) recommendations and Joanna Briggs Institute Critical (JBI) Appraisals guidelines. Eighty-three studies focused on efficacy, safety and tolerability of duloxetine were included in our systematic review. Studies were subdivided by clinical condition and evaluated individually. Thus, 32 studies of MDD, 11 studies of GAD, 17 studies of NP, 9 studies of FMS and 14 studies of SUI demonstrated that the measured outcomes indicate the suitability of duloxetine in the treatment of these clinical conditions. This systematic review confirms that the dual mechanism of duloxetine benefits the treatment of comorbid clinical conditions, and supports the efficacy, safety and tolerability of duloxetine in short- and long-term treatments.